A possible reason for non-proportionality of response in NaI:Tl and CsI:Tl scintillation crystals - Kudin, A.M.; Grinyov, B.V.; Gres', V.Yu.; Mitichkin, A.I. (Functional Materials, 2006)
It is known that the light yield L is not proportional to energy Е for many scintillation materials under excitation by external γ-rays. In contrast, L is proportional to Е for internal radiation sources. In this work, it has been shown that this contradiction can be eliminated if the non-proportionality is considered as a total result caused by two effects. First, the scintillation duration is shortened as the photon energy decreases, that results in increasing measured L/Е value at fixed signal formation time. Second, the presence of
dead layer results in the luminescence quenching near the crystal surface. In this concept, the response non-proportionality is considered as axial inhomogeneity of the scintillation efficiency depending on the radiation penetration depth Н. It has been shown that the valley in L/Е vs Е dependence near the K-edge of iodine absorption (the jump-like Н changing almost by ten times) disappears on the L/Е vs Н one. Известно, что световой выход L непропорционален энергии электронов Е для многих сцинтилляционных материалов при возбуждении внешними γ-квантами. В противоположность этому, L пропорционален Е для внутренних источников радиации. В работе показано, что это противоречие можно устранить, если непропорциональность выхода рассматривать как суммарный эффект двух факторов. Во-первых, длительность сцинтилляций сокращается с уменьшением энергии квантов, что приводит к увеличению измеряемой величины L/Е при фиксированном времени формирования сигнала. Во-вторых, наличие мертвого слоя приводит к тушению люминесценции вблизи поверхности кристалла. В таком подходе непропорциональность выхода трактуется как осевая неоднородность сцинтилляционной эффективности в зависимости от глубины Н проникновения излучений. Показано, что провал на зависимости L/Е vs Е около K-края поглощения йода, где Н изменяется скачком на порядок, исчезает на зависимости L/Е vs Н. Вiдомо, що свiтловихiд L не є пропорцiональним енергiї електронiв Е для багатьох сцинтиляцiйних матерiалiв при збудженнi зовнiшнiми γ-квантами. У протилежнiсть цьому, L є пропорцiональним Е для внутрiшнiх джерел радiацiї. У роботi показано, що це протирiччя можна усунути, якщо непропорцiональнiсть виходу розглядати як сумарний ефект двох чинникiв. По-перше, тривалiсть сцинтиляцiй скорочується зi зменшенням енергiї квантiв, що приводить до збiльшення вимiрюваної величини L/Е при фiксованому часi формування сигналу. По-друге, наявнiсть мертвого шару спричиняє гасiння люмiнесценцiї поблизу поверхнi кристалу. При такому пiдходi непропорцiональнiсть виходу трактується як осьова неоднорiднiсть сцинтиляцiйної ефективностi в залежностi вiд глибини Н проникнення радiації. Показано, що провал на залежностi L/Е vs Е поблизу K-краю поглинання йоду, де Н змiнюється стрибком на порядок, зникає на залежностi L/Е vs Н.